Evaluation of sleep quality, excessive daytime sleepiness and associated factors in medical students - a systematic review (International Seven Journal of Multidisciplinary, 2023)
Objective: To systematically review the scientific literature from the last 20 years about the EDS and Medical Students dyad, in order to understand the relationship and the impacts on the health of these individuals. Methods: A systematic review was conducted in December 2020 in PubMed and SciELO using the descriptors "Sleep Disorders", "Excessive Daytime Sleepiness" (EDS) and "Medical Students". Inclusion criteria were: original articles from the last 20 years, in English, Portuguese and Spanish, and, as exclusion criteria, failure to meet inclusion eligibility. Result: The analysis of the studies demonstrates a direct relationship between the academic responsibilities of medical students and sleep deprivation. As a consequence, this course presents itself as a trigger of poor sleep quality indices and EDS, as well as social and psychological consequences for academics. Conclusion: The great demands of the medical course may lead to sleep disorders due to the difficulty in reconciling them with individual health, causing psychopathological symptoms and mental exhaustion. Thus, measures that balance the student's routine with academic needs are important. DOI: 10.56238/isevmjv1n2-005